Enhancing rural connectivity through an extended internet cafés business models - Idongesit Williams; Patrick Ohemeng Gyaase; Morten Falch (International Telecommunications Society (ITS), 2012)
This paper discusses the potentials of an adaptation of the Internet café business model adopted for Internet access in African cities to improve rural Internet access through a partnership between the public and private sectors. The rural areas in most developing countries e lack of Internet connectivity due to commercial unviability of such investment by the private sector alone.. The modernization theory is used to support the concept that the availability of Internet services in rural can be catalyzed if an Adaptation of the Internet cafés business model incorporating the public participation are replicated in the rural areas. . A study is carried out in Ghana, where the market players in the Internet café operations to ascertain the potential viability of public - private partnership in the provisioning of internet access in the rural areas in Ghana. A new business model in the form of Public Private Partnership is proposed that will facilitate the extension of Internet cafés into rural areas to enhance rural connectivity.
Keywords: 330